'Like us' or 'One of us': Tensions between Liberal and Communitarian Values in EU-Ukraine Relations. Issue 2 (September 2016) - Krasnodębska, Molly
The article compares the Eastern Neighbourhood policies of the two founders of the Eastern Partnership (EaP), Poland and Sweden. It focuses on the two countries' approaches towards Ukraine during the preparations of the EU-Ukraine Association Agreement (AA) in late 2013. The article argues that while both Sweden and Poland have a strongly value-driven approach towards Ukraine, their foreign policies are guided by two different understandings of values: a liberal and a communitarian understanding. Sweden's foreign policy, which is based on liberal values, focuses on the promotion of certain 'universal' norms connected to human rights, democracy, and good governance in its neighbourhood, offering assistance in reforms to those countries which show commitment to these norms. By contrast, Poland's approach towards the Eastern neighbourhood is guided by a communitarian understanding of solidarity and 'kinship duty' based on perceptions of a common heritage and a shared regional identity. From the different understandings of values follow different logics of action. For Sweden, Ukraine's inclusion into the EU's institutional structures, e.g. through the AA, is conditioned on Ukraine's democratic performance and approximation to European standards. Poland, on the other hand, views Ukraine's inclusion into EU structures as a precondition for the country's success in reforms. Because of these different logics, the EaP at large, which is shaped by both liberal and communitarian values, entails intrinsic tensions. These tensions are arguably more problematic than tensions between values and interests, to which scholars often attribute the EaP's shortcomings.